IMPROVING INTERCULTURAL COMMUNICATION OF EFL STUDENTS THROUGH SHORT STORIES - Mardanova Zilola Fatxullo qizi (International Engineering Journal For Research & Development, 2021)
At present, globalization and foreign languages learning are the most essential and inseparable things. Learning of communication in a foreign language is very important to be aware of culture, life style, literature, history of foreign country and etc. This paper is based on useful instructions and how to use storytelling as a means of improving intercultural communication in EFL classes. Storytelling may be a new concept for teachers that have no experience in teaching and an informal technique for experienced teachers. The article discusses the importance of storytelling in developing oral communication in foreign language learning for EFL students. Reading short stories is comparable to the process of intercultural communication, as the author and the reader are representatives of different cultures. Intercultural communication through stories has a number of features compared to real communication, the identification of which is the purpose of the research presented in the article. Furthermore, this article shows that learners have a positive attitude towards working with the story, and that they get a deeper understanding of the story and the concepts in focus. This way reveals that there has been a development in the learners’ intercultural competence.